PAI‐1 induction during kidney injury promotes fibrotic epithelial dysfunction via deregulation of klotho, p53, and TGF‐β1‐receptor signaling. Issue 7 (10th June 2021) - Gifford, Cody C.; Lian, Fei; Tang, Jiaqi; Costello, Angelica; Goldschmeding, Roel; Samarakoon, Rohan; Higgins, Paul J.
Abstract: Renal fibrosis leads to chronic kidney disease, which affects over 15% of the U.S. population. PAI‐1 is highly upregulated in the tubulointerstitial compartment in several common nephropathies and PAI‐1 global ablation affords protection from fibrogenesis in mice. The precise contribution of renal tubular PAI‐1 induction to disease progression, however, is unknown and surprisingly, appears to be independent of uPA inhibition. Human renal epithelial (HK‐2) cells engineered to stably overexpress PAI‐1 underwent dedifferentiation (E‐cadherin loss, gain of vimentin), G2/M growth arrest (increased p‐Histone3, p21), and robust induction of fibronectin, collagen‐1, and CCN2. These cells are also susceptible to apoptosis (elevated cleaved caspase‐3, annexin‐V positivity) compared to vector controls, demonstrating a previously unknown role for PAI‐1 in tubular dysfunction. Persistent PAI‐1 expression results in a loss of klotho expression, p53 upregulation, and increases in TGF‐βRI/II levels and SMAD3 phosphorylation. Ectopic restoration of klotho in PAI‐1‐transductants attenuated fibrogenesis and reversed the proliferative defects, implicating PAI‐1 in klotho loss in renal disease. Genetic suppression of p53 reversed the PA1‐1‐driven maladaptive repair, moreover, confirming a pathogenic role for p53 upregulation in this context and uncovering a novel role for PAI‐1 in promoting renal p53 signaling. TGF‐βRI inhibition also attenuated PAI‐1‐initiated epithelial dysfunction, independent of TGF‐β1 ligand synthesis. Thus, PAI‐1 promotes tubular dysfunction via klotho reduction, p53 upregulation, and activation of the TGF‐βRI‐SMAD3 axis. Since klotho is an upstream regulator of both PAI‐1‐mediated p53 induction and SMAD3 signaling, targeting tubular PAI‐1 expression may provide a novel, multi‐level approach to the therapy of CKD.